2022
DOI: 10.3390/v14050873
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variants in Paraguay: Detection and Surveillance with an Economical and Scalable Molecular Protocol

Abstract: SARS-CoV-2 variant detection relies on resource-intensive whole-genome sequencing methods. We sought to develop a scalable protocol for variant detection and surveillance in Paraguay, pairing rRT-PCR for spike mutations with Nanopore sequencing. A total of 201 acute-phase nasopharyngeal samples were included. Samples were positive for the SARS-CoV-2 N2 target and tested with the Spike SNP assay to detect mutations associated with the following variants: alpha (501Y), beta/gamma (417variant/484K/501Y), delta (4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The primary outcome was SARS-CoV-2 detection and relative quantitation by cycle threshold (Ct) in self-vs health care worker-collected nasal swabs when tested with a real-time reverse transcriptase-polymerase chain reaction test with Emergency Use Authorization. RESULTS Among the study participants, 108 of 194 (55.7%) were male and the median age was 9 years (IQR,(6)(7)(8)(9)(10)(11). Of the 196 participants, 87 (44.4%) tested positive for SARS-CoV-2 and 105 (53.6%) tested negative by both self-and health care worker-collected swabs.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was SARS-CoV-2 detection and relative quantitation by cycle threshold (Ct) in self-vs health care worker-collected nasal swabs when tested with a real-time reverse transcriptase-polymerase chain reaction test with Emergency Use Authorization. RESULTS Among the study participants, 108 of 194 (55.7%) were male and the median age was 9 years (IQR,(6)(7)(8)(9)(10)(11). Of the 196 participants, 87 (44.4%) tested positive for SARS-CoV-2 and 105 (53.6%) tested negative by both self-and health care worker-collected swabs.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%
“…This assay was performed as described. 6,7 Usability Evaluation A set of usability questions was developed to determine whether all tasks associated with self-swabbing were completed correctly, whether participants required any assistance, how participants felt about self-swabbing, and whether participants understood the instructions (eAppendix in the Supplement). A portion of the questions were HCW facing; that is, the HCW conducting the study observed participant actions and responded to questions accordingly.…”
Section: Key Pointsmentioning
confidence: 99%
“…Specimens included 169 SARS-CoV-2–positive acute-phase samples collected as part of 3 ongoing studies to characterize SARS-CoV-2 variants in distinct patient populations: (1) acute infections in Paraguay (75 samples); (2) hospitalized adults in the Emory Healthcare System as part of the ongoing RSV in Older Adults and Pregnant women Study (ROAPS, 65 samples); and (3) individuals in the Atlanta area tested at the Emory/Children’s Laboratory for Innovative Assay Development (ELIAD) to confirm diagnostic test performance (29 samples). The Paraguay sample set has been described previously [ 9 ]. ROAPS samples included a mixture of nasopharyngeal swabs obtained at the time of hospitalization for standard-of-care clinical testing and nasal midturbinate swabs collected at enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acids were eluted from 400 µL of sample into 50 µL of elution buffer. All eluates had previously been tested in the N2RP rRT-PCR, a duplex assay targeting the N2 target in the SARS-CoV-2 genome and RNase P as an internal control [ 6 , 9 ]. Each sample was also tested in 2 different rRT-PCR assays of the spike single nucleotide polymorphism (Spike SNP) assay, including probes for (1) K417, 452R, 484K, and 501Y and (2) 452Q, 478K, and 490S, as previously described [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation